Content analysis of the environmental concepts contained within the biology book of the primary seventh grade - Mansoure, Nada (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The goals of this research is to recognize the environmental concepts that should be contained within the biology book of the primary seventh grade from the perspective of the biology teachers of the city of Tartus, and the degree of the presence of these concepts in the biology book. These concepts are represented as follows: (Genetics and the environment, Environmental pollution, Environmental balance, Natural resources, Population and the environment, Environmental problems). The researcher relied in her study of the results on the Descriptive Analytical Method, and the use of the Content Analysis method, to get to the main key and sub concepts contained within the biology book of the seventh grade in Syrian Arab Republic for the educational year of 2015/2016. The results showed that the environmental concepts that should be contained within the seventh grade biology book from the perspective of the biology teachers of the city of Tartus came out at a low degree, and the content analysis results indicated to the incompatibility in distributing the repetitions on the environmental concepts contained within the biology book of the seventh grade. The results also showed that the main concepts that was focused on was Natural Resources. Regarding these results, the researcher recommended giving the educational environmental concepts more attention and care for the students of the seventh grade. She also recommended showing local environmental problems and suggesting proper solutions for them.